Pertumbuhan dan Produksi Karkas Sapi Peranakan Ongole dan Simmental Peranakan Ongole Jantan yang Dipelihara secara Feedlot (Growth and Carcass Production of Ongole Crossbred Cattle and Simmental Ongole Crossbred Cattle Reared in a Feedlot System) - Mateus da Cruz de Carvalho; Soeparno (Sueparno); Nono Ngadiyono (Faculty of Animal Science, Universitas Gadjah Mada, 2010)
The purpose of the experiment was to determine the growth and carcass production of Ongole grade cattle (PO) and Simmental Ongole (SimPO) crossbred cattle kept in a feedlot system. Six PO cattle and six SimPO crossbredcattle with the respective initial body weight of PO 315.6±39.46 kg and SimPO 368.3±17.81 kg, were kept for 3 months and fed with concentrates, elephant grass, soybean hulls and cassava. At the end of treatment all cattle wereslaughtered. The observed variables included feed consumption, feed digestibility, daily weight gain, feed conversion, feed cost per gain, blood urea and blood glucose levels, carcass cuts weight, carcass yield, carcass percentage, carcasscomponent, and meat-bone ratio. The obtained data were analyzed using the t-test. The treatments significantly affected carcass weight and carcass percentage (P<0.05), but it did not affect on feed consumption, feed digestibility, average daily gain, feed conversion, feed cost per gain, blood urea and blood glucose levels, carcass component, and meat-bone ratio. In conclusion, the SimPO crossbred had higher carcass weight and carcass percentage, and the feed cost per gain more efficient compared to PO cattle.(Key words: Growth, Carcass, Ongole grade cattle, Simmental Ongole Crossbred cattle, Feedlot)